Development of cashless payments in the digital economy ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the main trends in the development of cashless payments in the context of the digital economy. It investigates the factors driving the growth of cashless payments, as well as the importance of payment infrastructure, bank cards, and modern technologies in ensuring the efficiency, speed, and stability of monetary circulation. Particular attention is paid to the role of digitalization in transforming the payment habits of the population and businesses.
Keywords: cashless payments; digital economy; payment infrastructure; bank cards; payment technologies; money circulation; financial innovations